Climbing The Value Chain in the Penang Cluster – A Multi Stakeholder Study - Tho, Lye King (2009)
The multi stakeholder study undertaken on the Penang Cluster is to evaluate which of the various Regional Innovation System factors – are perceived to play an important role in helping companies in the cluster climb the value chain. This study is done using primary data collected from interviews with respondents working from industry players in the cluster and also relevant authorities and other stakeholders (Governmental bodies, Consulting Firms, Non-Governmental Organizations) operating in the cluster. The results show that although all the respondents agree that the seven Regional Innovation System Factors – the more important or critical ones seem to be (1) Public Support & Community Involvement (2) The External Links (3) The Regional Technological Infrastructure & Staff Cooperation and Informal Community Networks. The results also indicate significant differences between respondents from industry and respondents from other stakeholders - based on the Kruskal Wallis test , at p< 0.05, the two RIS factors with significant differences in these two groups are 1) The Economic Links and Innovation in Penang and (2) Public Support and Community Involvement . In conclusion, the study indicates that there are certain factors within the Penang Cluster which have to be considered to by industry and government to help firms to climb up the value chain and these factors vary in importance for different stakeholders – of particular interest is the importance of community involvement as a factor to help in the moving up of the value chain.